Mesoporous hollow carbon spheres for lithium–sulfur batteries: distribution of sulfur and electrochemical performance - Juhl, Anika C.; Schneider, Artur; Ufer, Boris; Brezesinski, Torsten; Janek, Jürgen; Fröba, Michael (Beilstein Journal of Nanotechnology, 2016)
Hollow carbon spheres (HCS) with a nanoporous shell are promising for the use in lithium–sulfur batteries because of the large internal void offering space for sulfur and polysulfide storage and confinement. However, there is an ongoing discussion whether the cavity is accessible for sulfur. Yet no valid proof of cavity filling has been presented, mostly due to application of unsuitable high-vacuum methods for the analysis of sulfur distribution. Here we describe the distribution of sulfur in hollow carbon spheres by powder X-ray diffraction and Raman spectroscopy along with results from scanning electron microscopy and nitrogen physisorption. The results of these methods lead to the conclusion that the cavity is not accessible for sulfur infiltration. Nevertheless, HCS/sulfur composite cathodes with areal sulfur loadings of 2.0 mg·cm−2 were investigated electrochemically, showing stable cycling performance with specific capacities of about 500 mAh·g−1 based on the mass of sulfur over 500 cycles.
Keywords: carbon/sulfur composites; cycling stability; distribution of sulfur in pores; hollow carbon spheres; lithium–sulfur batteries